Poly(3, 4-ethylenedioxythiophene):dextran sulfate (PEDOT:DS) – A highly processable conductive organic biopolymer. (1st March 2015) - Harman, David G.; Gorkin, Robert; Stevens, Leo; Thompson, Brianna; Wagner, Klaudia; Weng, Bo; Chung, Johnson H.Y.; in het Panhuis, Marc; Wallace, Gordon G.
Graphical abstract: Abstract: A novel water-dispersible conducting polymer analogous to poly(3, 4-dioxythiophene):polystyrene sulfonate (PEDOT:PSS) has been chemically synthesized in a single reaction in high yield. PEDOT:DS, a new member of the polythiophene family, is composed of a complex between PEDOT and the sulfonated polysaccharide polyanion dextran sulfate. Drop-cast films of aqueous suspensions of the material display a native conductivity of up to 7 ± 1 S cm −1, increasing to 20 ± 2 S cm −1 after treatment with ethylene glycol and thermal annealing. Mass ratios of the precursors NaDS and EDOT were varied from 5:1 to 2:1 and a decrease in the NaDS:EDOT ratio produces tougher, less hygroscopic films of higher conductivity. Ultraviolet–visible spectroelectrochemistry yields spectra typical of PEDOT complexes. Cyclic voltammetry reveals that PEDOT:DS is electrochemically active from −1.0 to 0.8 V vs. Ag/Ag + in acetonitrile, with similar characteristics to PEDOT:PSS. Water dispersions of PEDOT:DS are successfully processed by drop casting, spray coating, inkjet printing and extrusion printing. Furthermore, laser etching of dried films allows the creation of patterns with excellent definition. To assess the cytotoxicity of PEDOT:DS, L-929 cells were cultured with a polymer complex concentration range of 0.002 to 0.2 g l −1 in cell culture medium. No significant difference is found between the proliferation rates of L-929 cells exposed to PEDOT:DS and those in plain medium after 96 h. However, PEDOT:PSS shows around 25% less cell growth after 4 days, even at the lowest concentration. Taken together, these results suggest PEDOT:DS has exceptional potential as an electromaterial for the biointerface.